Rasionalisme Intervensi Negara dalam Perekonomian: Analisis Konsep Kepemilikan Zakat - Muhammad Sabiq Azmi (Jurnal Ilmiah Ekonomi Islam, 2022)
This study examines the concept of zakat ownership in Indonesia and examines what interventions are carried out by the government as the highest state authority regarding zakat in Indonesia. This research uses normative descriptive research, namely research based on literature review which is described through descriptions using library sources such as books, journals, and laws and regulations related to the research topic. In this study, it is explained that the zakat system in Indonesia is regulated in Law Number 23 of 2011 concerning the management of zakat. Through this legislation, the concept of zakat management has become clearer with the establishment of the National Amil Zakat Agency (BAZNAS) as an official and independent institution in managing and empowering assets and wealth derived from zakat. The government as the highest state institution also participates in zakat management activities in Indonesia by carrying out various intervention activities such as drafting laws, conducting security, supervising zakat wealth to providing knowledge to the public about the importance of zakat in Indonesia.